2011
DOI: 10.1093/rheumatology/ker188
|View full text |Cite
|
Sign up to set email alerts
|

Laser Doppler perfusion imaging in systemic sclerosis impaired response to cold stimulation involves digits and hand dorsum

Abstract: In early SSc, the thermoregulation of finger skin is impaired, but only in advanced stages of microangiopathy does the skin of the hand dorsum show a vasomotor control failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 17 publications
3
34
1
Order By: Relevance
“…Therefore, for an accurate assessment of the functional flow in LDPI is necessary to test vasoreactivity. In fact, in our study after a cold test we have shown that perfusion of the hand dorsum of SSc patients has different characteristics in the three capillaroscopic patterns (Rosato et al, 2011c).…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, for an accurate assessment of the functional flow in LDPI is necessary to test vasoreactivity. In fact, in our study after a cold test we have shown that perfusion of the hand dorsum of SSc patients has different characteristics in the three capillaroscopic patterns (Rosato et al, 2011c).…”
Section: Discussionmentioning
confidence: 66%
“…However, a combination of all 3 techniques improves classification Mugii 9 127 NVC Red blood cell velocity was significantly associated with NVC findings. Patients with the scleroderma active and late NVC pattern showed a lower red blood cell velocity compared with scleroderma early pattern Rosato 10 40 LDI and NVC In early SSc, thermoregulation of finger skin is impaired. With progression of NVC damage, the abnormal microvascular response to cold stimulation also appears in the hand dorsum skin LDI: laser Doppler imaging; LDF: laser Doppler flowmetry; NFC: nailfold capillaroscopy; NVC: nailfold videocapillaroscopy; PPG: photoplethysmography.…”
Section: To the Editormentioning
confidence: 94%
“…3,4 Nailfold video capillaroscopy, also known as nailfold capillary microscopy (NCM), helps detect abnormal capillaries associated with CTD, such as systemic sclerosis. 3,4,6 Results of Ms. J' s blood work and NCM don't suggest underlying CTD or other underlying disorder, so Ms. J will be treated for PRP. 12…”
Section: Diagnostic Processmentioning
confidence: 99%
“…[2][3][4] Attacks are often painful and may be associated with paresthesia, numbness, and impaired hand function. 6 RP usually affects fingers and toes, but the nose, ears, and lips can be affected as well. 2…”
mentioning
confidence: 99%